[OP.7C.07] DIASTOLIC LEFT VENTRICULAR FUNCTION IN RELATION TO COLLAGEN-SPECIFIC URINARY AND SERUM COLLAGEN BIOMARKERS IN A GENERAL POPULATION. (September 2016) - Zhang, Z.; Ravassa, S.; Yang, W.Y.; Petit, T.; Petra, Z.; Lopez, B.; Wei, F.F.; Pontillo, C.; Thijs, L.; Jacobs, L.; Gonzalez, A.; Koeck, T.; et al.
Abstract : Objective: Moving from multidimensional urinary proteomic markers to single urinary collagen fragments and linking these fragments to serum biomarkers of myocardial collagen turnover may generate new insights in the pathophysiology of diastolic LV function. Design and method: In 782 randomly recruited Flemish (51.3% women; 50.5 years), we assessed diastolic LV function by echocardiography, sequenced urinary collagen I (uCI) and III (uCIII) fragments, and determined serum markers of collagen I synthesis (PICP, carboxyterminal propeptide of procollagen) and breakdown (CITP, carboxyterminal telopeptide) and the tissue inhibitor of matrix metalloproteinase type 1 (TIMP 1). Results: The correlation between uCI and uCIII markers was inverse. In multivariable-adjusted analyses with Bonferroni correction, among 70 urinary peptides, six uCI and two uCIII fragments remained associated with diastolic LV function. Peak e' and e'/a' decreased with two uCI markers (P< = 0.0075). E/e' increased with three uCI markers (P< = 0.0078), but decreased with one uCIII peptide (P = 0.0091). Peak A declined with two uCIII markers (P< = 0.0025). Based on age-specific echocardiographic criteria, 182 participants (23.3%) had diastolic LV dysfunction. Partial least squares discriminant analysis, confirmed association of abnormal and normal diastolic LV function with uCI and uCIII fragments. PICP, CITP and TIMP-1 increased in relation to uCI (P< = 0.0016), whereas these serum markers decreased in relation to uCIII (P< = 0.0006). Conclusions: By sequencing uCI and uCIII fragments and by linking diastolic LV function with urinary and serum collagen biomarkers and their interaction, our current findings generalize previous observations in selected patients to the population at large, thereby closing the gap between low-level diastolic LV dysfunction and overt diastolic heart failure.